Penanggulangan Sampah Masker Medis Sekali Pakai dengan Pendekatan “Village Health Volunteers” di Kota Surabaya Pada Masa Pandemi Covid-19 - Arimurti Kriswibowo; Bella Sintawati; Catharina Irene Pesica Kristianto; Tasya Noor Hidayati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This article aims to find out that a Village Health Volunteer approach can be an innovation in handling disposable medical mask waste in the city of Surabaya which incidentally cannot be recycled. This causes it to have the potential to transmit disease if disposable medical masks are reused. The problem in this study is focused on disposable medical mask waste that has not been handled properly from the government side, the community itself and future estimates if left continuously will cause the environment to become worse due to the risk of cross-contamination or biological hazards if polluting the environment. The research method used is literature review. The results of this study explain that the Village Health Volunteer approach can be a way between the government and the community to work together in dealing with health, in this case the handling of disposable medical mask waste. During this pandemic, the use of disposable medical masks by the public has increased so that the waste of disposable medical masks has increased and the risk of cross-contamination or biological hazards by disposable medical mask waste has increased healthy.